Repair of interstrand DNA crosslinks induced by oxidative stress and anti-cancer agents (Eurasian Journal of Ecology, 2019)
Abstract. Interstrand crosslinks (ICLs) occur when two complimentary strands of DNA are covalentlylinked together after exposure to crosslinking agents, therefore blocking the processes essential for cellsurvival such as DNA transcription, replication and recombination by preventing the strand separationand switching cell fate to apoptosis. Taking advantage of it, chemical agents such as cisplatin, mitomycinC and nitrogen mustards are widely used in chemotherapy against cancer and several hyperplasic diseases. However, cellular responses induced by ICLs and repair mechanisms counteracting their cytotoxiceffect can lead to the appearance of acquired resistance in cancer cells thus limiting the efficiency of thetreatment. In this review, we will discuss the main properties of several classes of ICL-forming agents andrecent advances in our understanding of the mechanisms of ICL repair. Due to the recent developmentson the repair mechanisms of various ICLs, our insight has broadened regarding the drug-specific formation and cellular processing of ICLs. Even though the main features of ICL repair remained the same, newplayers of repair machinery acting upon specific ICLs are being discovered. These new findings mayfurnish a basis to improve and adapt anticancer therapies by targeting DNA repair pathways in order tocounteract the development of resistance to anti-cancer treatments.Key words: DNA repair, oxidative stress, DNA crosslinks